Menthol reduces phototoxicity pain in a mouse model of photodynamic therapy. Issue 2 (February 2018) - Wright, Lisa; Baptista-Hon, Daniel; Bull, Fiona; Dalgaty, Faith; Gallacher, Michael; Ibbotson, Sally H.; Hales, Tim G.
Abstract : Abstract: Phototoxicity-induced pain is a major clinical problem triggered by light acting on photosensitising drugs or endogenous porphyrins, notably protoporphyrin IX (PpIX), an intermediary in heme biosynthesis. Protoporphyrin IX accumulates in individuals with erythropoietic protoporphyria and is elevated during photodynamic therapy subsequent to application of 5-aminolevulinic acid (ALA). Pain occurs during irradiation of PpIX and responds poorly to conventional analgesics. Our objective was to develop a model of PpIX phototoxicity pain and investigate the potential of menthol as an analgesic. Application of ALA to the tails of C57 black and SWISS white mice caused PpIX accumulation and nociception during irradiation (630 nm at 3.7 J/cm 2 ). Despite similar PpIX accumulation, C57 mice exhibited less pain behavior compared with SWISS mice because of light absorption by pigmentation. Irradiation of ALA-treated dorsal root ganglion neurons caused phototoxicity-evoked action potentials (APs) in both mouse strains. The antioxidant L-tryptophan increased the light dose required to elicit such APs. By contrast, the addition of keratinocytes to neuronal cultures decreased the threshold for APs, suggesting a requirement for proliferating cells. Inhibition of fatty acid amide hydrolase, selective antagonism of TRPV1 or the application of lidocaine or its quaternary derivative QX-314, reduced AP frequency, whereas antagonism of TRPA1 had no effect. These results suggest that products of singlet oxygen–mediated lipid peroxidation trigger nociceptor activation via TRPV1. Menthol inhibited phototoxicity-evoked APs and reduced pain behavior when applied topically to mice. These findings suggest that menthol might provide pain relief in patients experiencing PpIX–phototoxicity pain caused by photodynamic therapy or erythropoietic protoporphyria. Abstract : Supplemental Digital Content is Available in the Text.A mouse model of pain associated with protoporphyrin IX–induced phototoxicity was developed and used to identify menthol as a promising candidate for topical analgesia.